Three farces : Fitting for ladies ; A close shave (in collaboration with Maurice Desvallières) ; Sauce for the goose /: Fitting for ladies ; A close shave (in collaboration with Maurice Desvallières) ; Sauce for the goose. (2004) - Unknown
No abstract available